Long Complete Remission Achieved with the Combination Therapy of Cisplatin and Gemcitabine in a Patient with Aggressive Natural Killer Cell Leukemia - Justin LaPorte; Lawrence Morris; John Koepke (Case Reports in Hematology)
Aggressive natural killer cell leukemia (ANKL) is a rare and often lethal lymphoproliferative disorder. Patients may present with constitutional symptoms, jaundice, skin infiltration, lymphadenopathy, and hepatosplenomegaly. ANKL can progress quickly to multiorgan failure and survival is usually measured in weeks. Although a rapid and accurate diagnosis is critical, unfortunately there is no hallmark diagnostic marker of ANKL. We report a case of a 48-year-old male who was able to obtain a complete remission following cisplatin-based chemotherapy. We describe the details of the chemotherapy regimens used and a literature review of the treatment of ANKL.